Emocjonalność dziecka w wieku przedszkolnym a jego gotowość szkolna - Dmochowska, Halina (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The emotions, according to children and adults, are the subject of many deliberations made by educationalists, psychologists, and the parents. In following text the problem of emotional readiness of a child in pre-school age to undertake assignments arising due to school duties is risen. The pre-school/school threshold is an immense challenge for a child. The change of a social rank from pre-schooler to pupil requires adequate level of it’s psychological and physical development – with special consideration of social and emotional aspects. The school achievements and failures of a child are mainly determine by its emotional state. The role of teachers as well as parents is to support child in this matter.
Keywords: child in the early school age; child preschool; emotionality; emotions; school maturity